Tumor necrosis factor receptor-associated cycle syndrome: a case report and literature review - Li, Ziwei; Jing, Xiaoping; Zhang, Shuya; Liu, Tiantian; Guo, Qingyin (Frontiers in Pediatrics, 2023)
Recurring episodes of fever characterize tumor necrosis factor receptor-associated periodic syndrome (TRAPS) which is autosomal dominant. The primary symptoms of patients with TRAPS include prolonged fever, abdominal pain, muscle pain, and skin rashes. The prevalence of TRAPS appeared higher in Western countries than in Asian countries. Herein, we present the case of a 13year-old girl who experienced intermittent fever for 8 years, with episodes that occur every 2 years.The patient demonstrated periodic fever, headache, vomiting, rash, and elevated inflammatory marker levels during the disease course. A heterozygous C55Y mutation was identified via a direct DNA sequencing of her genomic DNA. This mutation is located in exon 4 of TNFRSF1A. Genetic studies of her sister and mother revealed that they possessed the C55Y heterozygous mutation without demonstrating any clinical signs, while the father did not. Further, we conducted a thorough assessment of the literature and compiled the information from the eight TRAPS case series.